Synthesis, antiviral evaluation and molecular docking studies of N 4 -aryl substituted/unsubstituted thiosemicarbazones derived from 1-indanones as potent anti-bovine viral diarrhea virus agents - Soraires Santacruz, Maria Cristina (2017)
A series of N4-arylsubstituted thiosemicarbazones derived from 1-indanones and a set of compounds lacking such substitution in the N4 position of the thiosemicarbazone moiety were synthesized and evaluated for their anti-bovine viral diarrhea virus (BVDV) activity. Among these, derivatives 2 and 15 displayed high activity (EC50 = 2.7 ± 0.4 and 0.7 ± 0.1 µM, respectively) as inhibitors of BVDV replication. Novel key structural features related to the anti-BVDV activity were identified by structure-activity relationship (SAR) analysis. In a previous study, the thiosemicarbazone of 5,6-dimethoxy-1-indanone (5,6-TSC) was characterized as a non-nucleoside inhibitor (NNI) of the BVDV RNA-dependent RNA polymerase. In the present work, cross-resistance assays were performed with the most active compounds. Such studies were carried out on 5,6-TSC resistant BVDV (BVDV-TSCr T1) carrying mutations in the viral polymerase. This BVDV mutant was also resistant to compound 15. Molecular docking studies and MM/PBSA calculations were performed to assess the most active derivatives at the 5,6-TSC viral polymerase binding site. The differences in the interaction pattern and the binding affinity of derivative 15 either to the wild type or BVDV-TSCr T1 polymerase were key factors to define the mode of action of this compound.